ASSESSMENT OF THE SOCIO-ENTREPRENEURIAL ENVIRONMENT FOR THE DEVELOPMENT OF HIGHER EDUCATION INSTITUTIONS - Saidov , Shohruh Mirzo (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
Establishing a socio-entrepreneurial approach and combining social innovation with traditional academic pursuits is something that higher education institutions (HEIs) are moving toward more and more. This article examines how HEIs can promote constructive social change by giving graduates the knowledge and perspective needed to deal with societal issues. The benefits of a socio-entrepreneurial approach are examined in the literature review, which includes promoting inclusive education, helping graduates develop their social and entrepreneurial skills, and supporting social enterprise endeavors. Important elements for creating a strong socio-entrepreneurial ecosystem in higher education institutions (HEIs) are highlighted, including creating innovative curricula, encouraging cooperation with outside partners, and creating welcoming environments for student businesses. The article's conclusion highlights the difficulties and possibilities posed by this strategy and underlines the necessity of more study to maximize the influence of socio-entrepreneurial HEIs.